Studi Deskriptif Pesan Dakwah tentang Kesehatan Pada Konten Kreator Youtube dr. Zaidul Akbar - Hasanah, Nur; Ravico, Ravico; Firtanosa, Aan (Institut Agama Islam Negeri Kerinci, 2023)
dr. Zaidul Akbar was used YouTube as a media for da'wah by the health themes, YouTube is very good way to use for da’wah, because it presents interesting content. Then, da'wah messages with health themes will be easily accepted and understood. This research wanted to know about da'wah messages with health themes in videos that last 40:34 and 50:31 minutes durations which are uploaded on dr. Zaidul Akbar content. This reaserch was used a qualitative approach, and intsrument was used observation by the sense of sight, which means not asking questions, in other words, the researcher wanted to observe directly on Dr. Zaidul Akbar's YouTube content. After conducting the research, the researcher found that the results of da'wah messages about health in dr. Zaidul Akbar content, consists of 5 moral messages, 4 sharia messages, and 1 aqidah message. In both videos that are 40:34 and 50:31 minutes durations. Da'wah messages about health that are often discussed in their content are moral messages with a total of 5 discussions of moral messages. The health messages include explanations regarding the benefits of dates, spices such as ginger, turmeric, galangal, and lemongrass. dr. Zaidul Akbar also explained the benefits of almsgiving, prayer, fasting, doing good to others for physical, mental and other social health